Review of Munakahat Jurisprudence on Prospective Brides Staying at the Prospective Groom's House Before the Marriage Contract (Kisam Tradition in Berasang Village, Kisam Tinggi District, South Ogan Komering Ulu Regency) - Muhammad; Muhibban; Huslan Husada (Al-Mahkamah: Islamic Law Journal, 2024)
This research aims to examine Islamic jurisprudence regarding prospective brides who live in the prospective groom's house before the marriage ceremony, according to the Kisam tradition in Berasang Village, Kisam Tinggi District, South Ogan Komering Ulu Regency. This research uses the library study method, collecting primary data through observation and interviews, complemented by secondary data. This research found that the Kisam tradition is a cultural practice that is contrary to Islamic law because in its implementation there are elements of khalwat which are prohibited in Islam. In Islamic law, being together without a mahram is strictly prohibited because it can lead to adultery.